Exploration of GH94 Sequence Space for Enzyme Discovery Reveals a Novel Glucosylgalactose Phosphorylase Specificity - De Doncker, Marc; De Graeve, Chloé; Franceus, Jorick; Beerens, Koen; Křen, Vladimír; Pelantová, Helena; Vercauteren, Ronny; Desmet, Tom (Chembiochem, 2021)
The substantial increase in DNA sequencing efforts has led to a rapid expansion of available sequences in glycoside hydrolase families. The ever-increasing sequence space presents considerable opportunities for the search for enzymes with novel functionalities. In this work, the sequence-function space of glycoside hydrolase family 94 (GH94) was explored in detail, using a combined approach of phylogenetic analysis and sequence similarity networks. The identification and experimental screening of unknown clusters led to the discovery of an enzyme from the soil bacterium Paenibacillus polymyxa that acts as a 4-O-β-d-glucosyl-d-galactose phosphorylase (GGalP), a specificity that has not been reported to date. Detailed characterization of GGalP revealed that its kinetic parameters were consistent with those of other known phosphorylases. Furthermore, the enzyme could be used for production of the rare disaccharides 4-O-β-d-glucosyl-d-galactose and 4-O-β-d-glucosyl-l-arabinose. Our current work highlights the power of rational sequence space exploration in the search for novel enzyme specificities, as well as the potential of phosphorylases for rare disaccharide synthesis.
Keywords: Disaccharides; Molecular Structure; Models, Molecular; glycoside hydrolase family GH94; substrátová specifita; Glycoside Hydrolases; glykosidhydrolasy; sequence similarity networks; disacharidy; Phylogeny; Paenibacillus polymyxa; Substrate Specificity; glucosylgalactose phosphorylase; fylogeneze; molekulární modely; glycoside phosphorylase; molekulární struktura; enzyme discovery